STUDENT RESPONSE TO THE E-MODULE ACID BASE SOLUTION BASED ON CHEMICAL LITERACY - Fajar Naqsyahbandi; Syamsidar Syamsidar; Munnal Hani'ah (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2023)
Paradigm changes in the world of education demand innovation in classroom learning, including in chemistry subjects. This study aims to see students' responses to the product development of acid-based solution e-module based on chemical literacy. The type of research used is descriptive quantitative research. The research sampling technique used random sampling with the number of research subjects as many as 36 people who were students of the 11th grade in one of public Senior High School in Gowa Regency, South Sulawesi. The data obtained were processed quantitatively with the results of the study showing that the students' response to the acid-base e-module based on chemical literacy was 98.6% of students gave a good response, so this module was good for use in learning chemistry on acid-base material. Suggestions for further research are expected to proceed to the e-module effectiveness test stage.